Spatiotemporal distribution characteristics and attribution of extreme regional low temperature event - 封泰晨 张珂铨 苏海晶 王晓娟 龚志强 张文煜 (Chinese physics B, 2015)
Based on an objective identification technique for regional low temperature event（OITRLTE）, the daily minimum temperature in China has been detected from 1960 to 2013. During this period, there were 60 regional extreme low temperature events（ERLTEs）, which are included in the 690 regional low temperature events（RLTEs）. The 60 ERLTEs are analyzed in this paper. The results show that in the last 50 years, the intensity of the ERLTEs has become weak; the number of lasted days has decreased; and, the affected area has become small. However, that situation has changed in this century.In terms of spatial distribution, the high intensity regions are mainly in Northern China while the high frequency regions concentrate in Central and Eastern China. According to the affected area of each event, the 60 ERLTEs are classified into six types. The atmospheric circulation background fields which correspond to these types are also analyzed. The results show that, influenced by stronger blocking highs of Ural and Lake Baikal, as well as stronger southward polar vortex and East Asia major trough at 500-h Pa geopotential height, cold air from high latitudes is guided to move southward and abnormal northerly winds at 850 h Pa makes the cold air blow into China along diverse paths, thereby forming different types of regional extreme low temperatures in winter.